Appropriateness of Cotrimoxazole Prophylactic Therapy Among HIV/AIDS Patients in Public Hospitals in Eastern Ethiopia: A Retrospective Evaluation of Clinical Practice - Sisay, Mekonnen; Bute, Dida; Edessa, Dumessa; Mengistu, Getnet; Amare, Firehiwot; Gashaw, Tigist; Bihonegn, Temesgen (Frontiers in Pharmacology, 2018)
Background: Cotrimoxazole preventive therapy (CPT) is a feasible, cost-effective, and safe way of using cotrimoxazole intervention to reduce HIV/AIDS related morbidities and mortalities associated with opportunistic infections. This study, therefore, aims to evaluate CPT among HIV/AIDS patients in Jugel Hospital (JH), Harar and Dilchora Referral Hospital (DRH), Dire Dawa, Eastern Ethiopia. Methods: A retrospective cross sectional study was conducted to evaluate the use of cotrimoxazole as prophylactic therapy. In this study, 556 medical records of HIV/AIDS patients who had been taking CPT within Sep 2015-Aug 2016 were reviewed. Systematic random sampling was employed to obtain medical records from the sampling frame. Data were abstracted from the patient medical records using structured checklist customized from the World Health Organization (WHO) guideline. The data were entered into Epi-data 3.1 and exported to and analyzed with statistical Package for Social Sciences (SPSS) version 20. The finding was evaluated against the WHO guideline on the use of cotrimoxazole prophylaxis in HIV/AIDS patients. Results: Majority of the PLWHA who had been taking CPT were adults (95.9%), female (61.2%), married (43.7%), orthodox Christian (54.3%), and attended primary school (40.1%). At the start of CPT, most of the patients were at WHO clinical stage III (40.8%). The major comorbid illnesses identified were tuberculosis and pnemocystic-carini pneumonia. Initially, majority of the patients were at CD4 count of less than 350 cells/mm3 in both settings. Greater proportion of patients started CPT prior to initiating antiretroviral therapy (ART). Most of the patients took CPT for greater than 6 months. The primary reasons for premature discontinuation of CPT were CD4 greater than 350 cells/mm3, severe sulfa allergy and first trimester of pregnancy. Generally, the use of cotrimoxazole prophylaxis among the PLWHA was consistent with the WHO guideline for indication to start (n=519, 93.3%) and dose (n=552, 99.28%), despite the presence of contraindication in 6.65% patients. Conclusion: In reference to the WHO guideline, the use of CPT was found to be fully appropriate in more than two-thirds of PLWHA. Increased awareness of patients would optimize the CPT which may, in turn, improve utilization of cotrimoxazole and decrease the potential emergence of antimicrobial